2018
DOI: 10.1016/j.jamcollsurg.2017.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Post-Surgical Patients to Improve Opioid Disposal: A Before and After Quality Improvement Study

Abstract: Dissemination of the educational brochure improved disposal of unused opioids after surgery. This low-cost, easily implemented intervention can improve disposal of unused opioids and ultimately, decrease the amount of excess opioids circulating in our communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 22 publications
3
91
0
Order By: Relevance
“…[3][4][5][6][7][8] Interventions based on patient education have shown mixed effects with some studies showing no impact on appropriate disposal rates 9 and others showing positive benefits. 2,10,11 We conducted a single-institution prospective observational pilot study to determine 1) how postsurgical patients manage leftover opioids and 2) if the distribution of free home disposal packets and educational handouts increased the likelihood that patients would appropriately dispose of their leftover opioids. We hypothesized that the distribution of an opioid home disposal packet would increase patient-reported disposal intention.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Interventions based on patient education have shown mixed effects with some studies showing no impact on appropriate disposal rates 9 and others showing positive benefits. 2,10,11 We conducted a single-institution prospective observational pilot study to determine 1) how postsurgical patients manage leftover opioids and 2) if the distribution of free home disposal packets and educational handouts increased the likelihood that patients would appropriately dispose of their leftover opioids. We hypothesized that the distribution of an opioid home disposal packet would increase patient-reported disposal intention.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, previous studies have demonstrated that many patients inappropriately store and dispose of opioids, which can contribute to the diversion of unused opioids. 6,26 Third, given that the phone call was timed for days 7 to 10, when some patients were still routinely using opioids for pain control, the opioid requirements in the 30 day postoperative time period may have been higher than reported.…”
mentioning
confidence: 99%
“…14,15 Physician and patient education, smaller opioid prescriptions, non-opioid analgesic medications and improvement of appropriate opioid disposal have all been proposed recently as strategies to combat the opioid crisis. 14,[16][17][18] At London Health Sciences Centre, the Division of General Surgery identified opioid prescribing for acute pain as a priority area for improvement based on the 2017 Health Canada-Joint Statement of Action to Address the Opioid Crisis. 19 We designed the Standardization of Outpatient Procedure Narcotics (STOP Narcotics) initiative to standardize pain management approaches, with the objective of reducing excessive postoperative opioid prescriptions, and adequately controlling postoperative pain in outpatient general surgical procedures.…”
mentioning
confidence: 99%